Exploring the psychometric properties of the premonitory urge for tics scale (PUTS) and its association with psychiatric symptoms in Chinese children with tic disorders - Qiang Ding; Douglas W. Woods; Wen Xu; Ying Zhao; Shuqin Shen; Jinhua Sun (BMC, 2024)
Abstract Background The Premonitory Urge for Tics Scale (PUTS) is a common self-report measure of premonitory urges for patients with tic disorders. This study aims to evaluate the Chinese version of the PUTS (PUTS-C) and to explore its association with psychiatric symptoms in Chinese children diagnosed with tic disorders. Methods The psychometric evaluation involved 204 outpatients with tic disorders, aged 7-16 years, who were divided into two age groups: (7-10 years, n = 103; 11-16 years, n = 95). Results The PUTS-C demonstrated good internal consistency (McDonald'sω = 0.84) and two-week test-retest reliability (0.76). We observed a statistically significant correlation between the total PUTS-C score and various Yale Global Tic Severity Scale (YGTSS) subscales and total tic severity scores. The PUTS-C score also showed significant correlations with the Children Yale-Brown Obsessive Compulsive Scale (CY-BOCS), Screening Child Anxiety-Related Emotional Disorders (SCARED), and Children's Depression Inventory (CDI). Notably, premonitory urges independently predicted tic severity, beyond the influence of comorbid symptoms. A two-factor structure of the PUTS-C was identified in the total sample through factor analysis. Conclusions The PUTS-C possesses acceptable validity and good reliability. It appears that premonitory urges in Chinese patients with tic disorders are associated with obsessive-compulsive symptoms, anxiety, and depression, but can independently predict tic severity. Specific PUTS-C factors possibly related to motor and vocal tics. Future research should continue to investigate age-related differences and the association with tics and other sensory symptoms.